Population‐based cross‐sectional study on insulin resistance and insulin‐secretory capacity in Japanese school children. Issue 5 (6th April 2017) - Nishimura, Rimei; Sano, Hironari; Onda, Yoshiko; Tsujino, Daisuke; Ando, Kiyotaka; Ebara, Futoshi; Matsudaira, Toru; Ishikawa, Shinichiro; Sakamoto, Takuya; Tajima, Naoko; Utsunomiya, Kazunori
Abstract: Aims/Introduction: Little information is available regarding the status of insulin resistance (IR) and insulin deficiency (ID), as well as their relationship with obesity in children using the homeostasis model assessment (HOMA) in a population‐based setting. Materials and Methods: The study included a total of 445 ninth‐grade children participating in health check‐up programs implemented in Tsunan Town, Niigata, Japan (boys/girls, 252/193 [participation rates: 98.1/95.5%]). HOMA of insulin resistance ≥2.5 was defined as IR, and HOMA of β‐cell function <40 defined as ID. Results: The medians (25–75th percentiles) of HOMA of insulin resistance, HOMA of β‐cell function, Disposition Index and body mass index in boys were 1.2 (0.8–1.7), 64 (44–93), 52 (43–64) and 19.2 (18.0–20.7) kg/m 2, respectively, vs 1.5 (1.0–2.0), 86 (63–120), 60 (50–74) and 20.4 (18.9–22.0) kg/m 2, respectively, in girls. The HOMA of insulin resistance, HOMA of β‐cell function and Disposition Index values were significantly higher in the girls ( P  = 0.002, P  < 0.001 and P  < 0.001, respectively). Those with IR accounted for a significantly higher proportion of girls than boys (15.5/8.7%; P  = 0.027); those with obesity accounted for 9.9/10.7% (boys/girls); and those with IR and obesity accounted for 2.4/4.7%. Those with ID accounted for a significantly higher proportion of boys than girls (20.6/8.8%; P  = 0.001), whereas those with ID and obesity accounted for a very small proportion of either group (0.4/0.5%). Conclusions: The presence of IR was higher among the girls. In contrast, ID was more frequent among the boys. The infrequent presence of ID among children might support the presence of non‐obese type 2 diabetes adults in Japan. Abstract : Those with IR accounted for a significantly higher proportion of the girls (15.5%; n  = 30) than the boys (8.7%; n  = 22) ( P  = 0.027). In contrast, those with ID accounted for a significantly higher proportion of the boys than the girls (20.6 vs 8.8%; P  = 0.001).